Lecture Notes in Computer Science
DOI: 10.1007/978-3-540-72990-7_57
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Peer-to-Peer Storage Systems

Abstract: Abstract. This paper evaluates the performance of two schemes for recovering lost data in a peer-to-peer (P2P) storage systems. The first scheme is centralized and relies on a server that recovers multiple losses at once, whereas the second one is distributed. By representing the state of each scheme by an absorbing Markov chain, we are able to compute their performance in terms of the delivered data lifetime and data availability. Numerical computations are provided to better illustrate the impact of each sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…It is worth mentioning that the simulation analysis of [7] has concluded that the recovery time follows roughly a hypo-exponential distribution. As a consequence, the models presented in this paper are more realistic than those in [3,6]. We conclude this section by a word on the notation: a subscript "c" (resp.…”
Section: Assumptionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is worth mentioning that the simulation analysis of [7] has concluded that the recovery time follows roughly a hypo-exponential distribution. As a consequence, the models presented in this paper are more realistic than those in [3,6]. We conclude this section by a word on the notation: a subscript "c" (resp.…”
Section: Assumptionmentioning
confidence: 96%
“…In our previous work [6], simplifying assumptions have been considered while modeling the P2PSS, mainly that the recovery process is exponentially distributed. However, the implications of this assumption differ between replicated and erasure-coded systems.…”
Section: Related Work and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…P2P and large scale distributed storage systems have been analyzed by using Markov chains: for erasure codes in [2,7,6] and for replication in [14,5]. In this work, we model Hybrid Coding, Double Coding and Regenerating Codes with Markovian models.…”
Section: Related Workmentioning
confidence: 99%
“…We model the behavior of a block b in a lazy RS system by a CTMC, depicted in Figure 2(a). We did not use the chains classically used in the literature [2,7]. Our chain models the possible loss of the reconstructor p(b) during a reconstruction.…”
Section: Markov Chain Modelsmentioning
confidence: 99%